Bilateral Pallidal Stimulation for "Sticking‐Out Tongue" Feature in Patients With Primary Focal Tongue Protrusion Dystonia. Issue 2 (17th May 2013) - Chung, Jong Chul; Kim, Joo Pyung; Chang, Won Seok; Kim, Hae Yu; Chang, Jin Woo
<x xml:space="preserve">Abstract</x> Introduction Tongue protrusion dystonia can cause difficulty with speech, mastication, breathing, and swallowing. Deep brain stimulation (DBS) of the globus pallidus internus (GPi) is a widespread therapeutic alternative for treating medically refractory dystonia. To our knowledge, detailed reports regarding DBS for tongue protrusion dystonia are rare. In this report, we describe two patients with "sticking out" tongue protrusion who had undergone bilateral GPi DBS. Methods Operations were performed with surface electromyographic (EMG) monitoring, microelectrode recording, and macrostimulation to identify the point at which tongue kinetic cells respond most effectively. The most effective location for active contacts was identified according to burst EMG response in the posteroventral GPi. Results Two years after DBS, total Burke, Fahn, and Marsden Dystonia Rating Scale scores of two patients were improved from 12.5 to 1 (92.0%) and from 13 to 1 (92.3%), respectively. One 58‐year‐old woman who lost 7 kg weight from not eating well improved enough to eat solid food and became free from choking. Another 54‐year‐old woman who had dysarthria and mumbled could speak more fluently and would not have complained difficulty in reading any more. Conclusion Stimulation on posteroventral GPi for patients with idiopathic "sticking‐out" tongue movement changes EMG pattern in orofacial muscles. This fact supports a reason for modulation of unknown circuit connecting tongue‐specific area in motor cortex, and basal ganglia.